Mother Mary in the Hindu pantheon among Portuguese Gujarati families - Cachado, R.; Lourenço, I. (Shifting transnational bonding in Indian diaspora, 2020)
The South Asian diaspora in Portugal is diverse in nationalities and religious practices. The most prominent population is the Hindu-Gujarati, living in Portugal since the late 1970s. This migration was boosted by the decolonization of a former Portuguese colony, Mozambique, to where Indians had migrated from India. Anchored in long-term fieldwork, this chapter concentrates on Hindu practices that incorporate elements of Portuguese Catholicism, specifically a representation of Mother Mary, Our Lady of Fatima. These practices point to hybridization processes among transnational communities and, in that sense, to challenge dominant visions about Hindu diaspora. To illustrate our argument, we will present this population and its cultural practices, to better understand this interest on Our Lady of Fatima, a Portuguese title for the Virgin Mary. We will specifically make an account of the forms this worship takes.